Thermal and Chemical Stability of n-Hexadecanethiol Monolayers on Au(111) in O2 Environments. (10th October 2016) - Cometto, Fernando P.; Ruano, Gustavo; Soria, Federico A.; Calderón, C. Andrea; Paredes-Olivera, Patricia A.; Zampieri, Guillermo; Patrito, E. Martín
Abstract: Understanding the mechanisms of degradation of self-assembled monolayers (SAM) is required for their use in molecular devices and in general in long term applications. In this context, we investigated the thermal and chemical stability of n -hexadecanethiolate (C16T) monolayers on Au(111) exposed to O2 . The degradation of the monolayers was followed by electrochemical (EC) techniques, surface enhancement Raman spectroscopy (SERS) and high resolution photoemission spectra (HR-XPS). The C16T monolayers were heated both under N2 and O2 flux up to 480 K for different times. The degradation of the SAM in the presence of O2 is characterized by the appearance of oxidized sulfur species and sulfur atoms on the surface. The formation time in the dipping solution also affects the thermal stability of the monolayer. Molecular dynamics (MD) simulations and density functional theory (DFT) calculations were performed to elucidate the possible degradation mechanisms. MD shows that O2 molecules easily penetrate the monolayer reaching the Au surface. The DFT calculations identified two oxidation mechanisms which involve the S atom and the alpha carbon of the alkylthiolate. Both mechanisms are very exothermic. The oxidation of the sulfur atom produces a sulfinate which does not alter the monolayer structure. On the contrary, the oxidation of the alpha carbon induces the breakage of the SC bond, the adsorption of atomic S and the desorption of the alkyl chain as an aldehyde.